Pengembangan Desain Interior Kelas PAUD Berbasis Pendidikan Karakter terhadap Perkembangan Emosi Anak Usia 5-6 Tahun di RA Nurbaiti Kota Padang - Desmariani, Evi; Jendriadi, Jendriadi; Misrayeti, Misrayeti; Rahmawati, Oktavia (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This research is motivated by the findings during observations when learning activities take place children are not too focused on the teacher's explanation, tested when the teacher explains learning material children prefer to talk with friends, when eating a lot of walking, not orderly when praying and children like to scream. Then the classroom where the daily learning process has not been designed according to the needs of children, especially the interior design of the attic, walls and floors in instilling character values. For this reason, it is necessary to develop interior design for PAUD classes based on character education for the emotional development of children aged 5-6 years. The purpose of developing this interior design is to create a classroom atmosphere that is comfortable, safe and fun for children during the learning process and this interior design can also make it easier for children to receive messages about good character values for the emotional development of children aged 5-6 years. This research is an R&D (Research and Development) study with a 4D model, namely define, design, develop, disseminate. The instrument used in this research is the interior design validation instrument sheet. This research was conducted in the odd semester of 2021-2022. The results of the validation results for the development of character education-based PAUD classroom interior design on emotional development with two validators were stated to be very valid with a design feasibility percentage (96.4%), practitioners (96.9%) proved that it was very effective for the emotional development of children aged 5-6 years at RA Nurbaiti Padang City.